Heat Transfer Performance of a Downhole Electric Tubular Resistive Heater - Yu Chen; Hao Zeng; Jianli Wang; Haoran Chen; Jianjun Zhu (Applied Sciences, 2022)
A downhole electric tubular resistive heater is proposed for the oil-shale in situ resorting. After flowing through a set of heating tubes, the outlet temperature and the flow rate of the injected gas can be conveniently adjusted to match the requirement of the pyrolysis temperature of the oil shale. The calculation demonstrates the effects of the inner diameter, the length of the heating tube, and the inlet flow rate on the heat transfer performance of the electric heater. It was found that, compared with the armored electric heaters, even with a small inject flow rate of 5 Nm3/min, the convective heat transfer coefficient of the inner flow exceeds 300 W/m2 K, resulting in a much smaller thermal resistance. The outlet temperature of the heating gas can conveniently reach up to 900 °C with the absence of the complex structure of enhanced fins. Though the pressure loss is relatively larger under a high flow rate, the comprehensive index is still 40% higher, indicating that the present tubular electric heater is a promising candidate to deal with complex downhole conditions.